An Update to Enterococcal Bacteremia: Epidemiology, Resistance, and Outcome - Jafari, Sirous; Abdollahi, Alireza; Sabahi, Marjan; Salehi, Mohammadreza; Asadollahi-Amin, Ali; Hasannezhad, Malihe; Seifi, Arash (Infectious Disorders - Drug Targets, 2022)
Background: An increase in resistant gram-positive cocci, especially enterococci, requires an epidemiologic re-assay and its results may affect empirical treatments for these infections. Objective: In this study, we investigated the microbial epidemiology and resistance pattern of enterococcal bacteremia. Methods: This study was a cross-sectional study that investigated all cases of positive blood cultures with Enterococcus spp. at a tertiary referral colligates hospital in Tehran in 2018. Results: Enterococcus spp. was isolated from blood cultures of a total of 73 patients. Most of the patients were male i.e: 42 (57.7%). The mean age of the patients was 58.8 (±18.8) years. Hospital- acquired infection was the most prevalent type of infection involving enterococcal bacteremia (80.8%) compared with community-acquired (6.7%) and the health care-associated one (12.3%). Renal failure and cancer were the most underlying disease in E. faecalis and E. faecium, respectively. Mortality for Vancomycin-resistant enterococci (VRE) was approximately two times more than the sensitive ones. Between the dead/alive groups, the following items were significantly different (P.Value<0.05): Vancomycin resistance for enterococcus isolated, immunodeficiency as an underlying disease, Mechanical ventilation, hospitalization period, and the empiric regimen. Conclusion: Increased antibiotic-resistant strains, especially Vancomycin-resistant enterococci (VRE), pose a serious threat to the general public, especially hospitalized patients, causing an increase in mortality. Surveillance of microorganisms and antimicrobial resistance is a crucial part of an efficient health care system.
Keywords: microorganisms